Neurolinguistik Umpatan: Studi Kasus Zoonim Sebagai Julukan Manusia Dalam Konteks Pragmatik - Wahyu, Yuni Sri (Universitas Wijaya Kusuma Surabaya, 2025)
AbstractThis study aims to find out the neurolinguistics of zoonymic swear words as human nicknames in a pragmatic context. This study uses qualitative descriptive with a case study method to explore the use of zoonyms as human nicknames in the social interaction of Javanese society. This study uses a phenomenological approach which understands the subject's experience of a zoonymic swearing event which has become a habit thrown by the people of Gambiran Village RT 02/RW 01 every time they communicate, especially when anger arises, the speaker does not hesitate to say zonim instead of the speaker's name with an indecent name or is equated with an animal. The data collection techniques in this study were participatory observation and in-depth interviews with informants who often used or received zoony-based nicknames in interaction. The sample in this study is part of the population of the Gambiran sub-district, namely the village of Gambiran RT 02 RW0 1 whose object consists of children, adolescents, adults and the elderly. The results of this study were obtained that there were 9 zonim words (Bangke, Budeng, Bedes, Mbote metu ketigo, Tuyul, Ketek, Jaran, Nyambik, Pig, Dog). So, it can be concluded that in a pragmatic context, the speech act of the Javanese people is collapsing, one of which is in Gambiran Village RT 02/RW 01.Keywords: Neurolinguistics, Zoonyms, Humans, Pragmatics